Division of Exponents with the Same Base

When we encounter exercises or expressions with terms that have the same base and between them the sign of division or fraction line, we can subtract the exponents.
We will subtract the exponent in the denominator from the exponent in the numerator.
That is:
"exponent of the denominator - exponent of the numerator" = new exponent
The result obtained from the subtraction is the new exponent and we will apply it to the original base.

Formula of the property:

aman=a(mn)\frac {a^m}{a^n} =a^{(m-n)}

This property also concerns algebraic expressions.

Suggested Topics to Practice in Advance

  1. Multiplying Exponents with the Same Base

Practice Power of a Quotient Rule for Exponents

Examples with solutions for Power of a Quotient Rule for Exponents

Exercise #1

2423= \frac{2^4}{2^3}=

Video Solution

Step-by-Step Solution

Let's keep in mind that the numerator and denominator of the fraction have terms with the same base, therefore we use the property of powers to divide between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} We apply it in the problem:

2423=243=21 \frac{2^4}{2^3}=2^{4-3}=2^1 Remember that any number raised to the 1st power is equal to the number itself, meaning that:

b1=b b^1=b Therefore, in the problem we obtain:

21=2 2^1=2 Therefore, the correct answer is option a.

Answer

2 2

Exercise #2

9993= \frac{9^9}{9^3}=

Video Solution

Step-by-Step Solution

Note that in the fraction and its denominator, there are terms with the same base, so we will use the law of exponents for division between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} Let's apply it to the problem:

9993=993=96 \frac{9^9}{9^3}=9^{9-3}=9^6 Therefore, the correct answer is b.

Answer

96 9^6

Exercise #3

Insert the corresponding expression:

13171314= \frac{13^{17}}{13^{14}}=

Video Solution

Step-by-Step Solution

To solve the expression 13171314 \frac{13^{17}}{13^{14}} , we use the Power of a Quotient Rule for Exponents. This rule states that aman=amn \frac{a^m}{a^n} = a^{m-n} , where a a is a non-zero number, and m m and n n are integers.


In the given expression, a=13 a = 13 , m=17 m = 17 , and n=14 n = 14 . Applying the power of a quotient rule, we perform the following calculation:


Subtract the exponent in the denominator from the exponent in the numerator: 1714=3 17 - 14 = 3 .


This simplification leads us to:

131714=133 13^{17-14} = 13^3


Therefore, the final simplified expression is 133 13^3 .

Answer

133 13^3

Exercise #4

Simplify the following:

a4a6= \frac{a^4}{a^{-6}}=

Video Solution

Step-by-Step Solution

Since a division operation between two terms with identical bases is required, we will use the power property to divide terms with identical bases:

cmcn=cmn \frac{c^m}{c^n}=c^{m-n} cmcn=cmn \frac{c^m}{c^n}=c^{m-n} Note that using this property is only possible when the division is performed between terms with identical bases.

We return to the problem and apply the power property:

a4a6=a4(6)=a4+6=a10 \frac{a^4}{a^{-6}}=a^{4-(-6)}=a^{4+6}=a^{10} Therefore, the correct answer is option C.

Answer

a10 a^{10}

Exercise #5

Insert the corresponding expression:

81688= \frac{8^{16}}{8^8}=

Video Solution

Step-by-Step Solution

The given expression is 81688 \frac{8^{16}}{8^8} . To solve this, we apply the Power of a Quotient Rule for Exponents.

This rule states that when dividing two exponential expressions with the same base, we subtract the exponent of the denominator from the exponent of the numerator. Mathematically, it can be expressed as:

  • aman=amn \frac{a^m}{a^n} = a^{m-n}

In this problem, the base 8 8 is the same in both the numerator and the denominator, so we can apply this rule.

Subtract the exponent of the denominator from the exponent of the numerator:

  • 168=8 16 - 8 = 8

Therefore, the simplified form of the given expression is:

  • 88 8^8

Thus, the answer is 88 8^8 .

Answer

88 8^8

Exercise #6

Insert the corresponding expression:

8489= \frac{8^4}{8^9}=

Video Solution

Step-by-Step Solution

To simplify the expression 8489 \frac{8^4}{8^9} , we apply the rule of exponents for division:

  • The quotient rule for exponents is aman=amn \frac{a^m}{a^n} = a^{m-n} .

Since both the numerator and the denominator have the same base (8), we can apply this rule directly:

8489=849 \frac{8^4}{8^9} = 8^{4-9}

Thus, the resulting expression is 85 8^{-5} .

Reviewing the choices given:

  • Choice 1: 894 8^{9-4} which equals 85 8^5 , is incorrectly stating the subtraction order.
  • Choice 2: 849 8^{\frac{4}{9}} is incorrect, as it represents a different operation (taking the root) rather than division of exponents.
  • Choice 3: 849 8^{4-9} is correct, as it correctly applies the quotient rule for exponents.
  • Choice 4: 84×9 8^{4\times9} suggests multiplication of exponents, not applicable here.

Therefore, the correct answer is Choice 3: 849 8^{4-9} , which simplifies to 85 8^{-5} .

Answer

849 8^{4-9}

Exercise #7

Insert the corresponding expression:

17161720= \frac{17^{16}}{17^{20}}=

Video Solution

Step-by-Step Solution

To solve the expression 17161720 \frac{17^{16}}{17^{20}} , we can apply the Power of a Quotient Rule for Exponents. This rule states that when you divide two exponents with the same base, you can subtract the exponents to simplify the expression.

The given expression is:

17161720 \frac{17^{16}}{17^{20}}

According to the Quotient Rule for Exponents, this expression can be simplified as:

171620 17^{16-20}

Here's the step-by-step breakdown:

  • The base of both the numerator and the denominator is the same, that is, 17.
  • According to the rule, subtract the exponent in the denominator from the exponent in the numerator: 1620 16 - 20 .
  • This gives us the exponent: 4 -4 .

So, the simplified expression is:

174 17^{-4}

However, as requested, we should express this as:

171620 17^{16-20}

The solution to the question is:

171620 17^{16-20}

Answer

171620 17^{16-20}

Exercise #8

Insert the corresponding expression:

259252= \frac{25^9}{25^2}=

Video Solution

Step-by-Step Solution

To solve the expression 259252 \frac{25^9}{25^2} , we will use the Power of a Quotient Rule for Exponents. According to this rule, when dividing like bases, we subtract the exponents.


  • am÷an=amn a^m \div a^n = a^{m-n}


In the given expression, the base 25 25 is the same for both the numerator and the denominator. Therefore, we can apply the rule as follows:


  • Identify the exponents: m=9 m = 9 and n=2 n = 2 .

  • Subtract the exponents: 92=7 9 - 2 = 7 .

  • Write the result as a single power of the base: 257 25^7 .


Thus, the expression 259252 \frac{25^9}{25^2} simplifies to 257 25^7 .


The solution to the question is: 25^7

Answer

257 25^7

Exercise #9

Insert the corresponding expression:

57510= \frac{5^7}{5^{10}}=

Video Solution

Step-by-Step Solution

To solve the expression 57510 \frac{5^7}{5^{10}} , we need to apply the Power of a Quotient Rule for Exponents. This rule states that when dividing like bases, you subtract the exponents:

aman=amn \frac{a^m}{a^n} = a^{m-n} .

In this particular case, the base is 5, and the exponents are 7 and 10. Using the rule, we subtract the exponent in the denominator from the exponent in the numerator:

  • Numerator exponent = 7
  • Denominator exponent = 10

Therefore, we get:

5710 5^{7-10} .

In conclusion, the simplified form of the given expression is:
53 5^{-3} .

The solution to the question is: 5710 5^{7-10} .

Answer

5710 5^{7-10}

Exercise #10

Insert the corresponding expression:

60606042= \frac{60^{60}}{60^{42}}=

Video Solution

Step-by-Step Solution

To solve the expression 60606042 \frac{60^{60}}{60^{42}} , we need to apply the Power of a Quotient Rule for Exponents. This rule states that when dividing like bases, we subtract the exponents. In mathematical terms, for any non-zero number a a , and integers m m and n n , aman=amn \frac{a^m}{a^n} = a^{m-n} .

Applying this rule to our problem:

  • We have the same base:60 60 .

  • We subtract the exponent in the denominator from the exponent in the numerator: 606042 60^{60-42} .

  • This simplifies the expression to 6018 60^{18} .

Therefore, the solution to the question is: 6018 60^{18} .

Answer

6018 60^{18}

Exercise #11

Insert the corresponding expression:

915910= \frac{9^{15}}{9^{10}}=

Video Solution

Step-by-Step Solution

To solve the expression 915910 \frac{9^{15}}{9^{10}} , we will use the Power of a Quotient rule for exponents, which states that aman=amn \frac{a^m}{a^n} = a^{m-n} . This rule applies when both the numerator and the denominator have the same base.

In our problem, both the numerator and the denominator have the base 9, hence we can apply the rule:

  • Identify the exponents: The exponent in the numerator is 15, and the exponent in the denominator is 10.
  • Apply the Power of a Quotient rule by subtracting the exponent of the denominator from the exponent of the numerator:
    91510 9^{15-10}
  • Calculate the result of the subtraction:
    1510=5 15 - 10 = 5
  • Thus, the simplified form of the expression is:
    95 9^5

The solution to the question is: 95 9^5

Answer

95 9^5

Exercise #12

Insert the corresponding expression:

5959 \frac{5^9}{5^9}

Video Solution

Step-by-Step Solution

To solve this problem, we apply the Power of a Quotient Rule for exponents. This rule is applicable when both the numerator and the denominator of a fraction have the same base. The rule states:


aman=amn \frac{a^m}{a^n} = a^{m-n}


For our problem, the expression is:


5959 \frac{5^9}{5^9}


In this expression, the base a a is 5 5 , m m is 9 9 , and n n is also 9 9 . We apply the rule as follows:


5959=599 \frac{5^9}{5^9} = 5^{9-9}


Calculating the exponent:


99=0 9 - 9 = 0


So the expression becomes:


50 5^0


Any number raised to the power of 0 is 1, but in this context, we are simply reducing the original expression to its simplest form. Therefore, 50 5^0 is the correct answer.


The solution to the question is: 50 5^0

Answer

50 5^0

Exercise #13

3532= \frac{3^5}{3^2}=

Video Solution

Step-by-Step Solution

Using the quotient rule for exponents: aman=amn \frac{a^m}{a^n} = a^{m-n} .

Here, we have 3532=352 \frac{3^5}{3^2} = 3^{5-2}

Simplifying, we get 33 3^3

Answer

33 3^3

Exercise #14

5654= \frac{5^6}{5^4}=

Video Solution

Step-by-Step Solution

Using the quotient rule for exponents: aman=amn \frac{a^m}{a^n} = a^{m-n} .

Here, we have 5654=564 \frac{5^6}{5^4} = 5^{6-4} . Simplifying, we get 52 5^2 .

Answer

52 5^2

Exercise #15

Insert the corresponding expression:

5358= \frac{5^3}{5^8}=

Video Solution

Step-by-Step Solution

We need to simplify the expression 5358 \frac{5^3}{5^8} using the rules of exponents. Specifically, we will use the power of a quotient rule for exponents which states that when you divide like bases you subtract the exponents:

aman=amn \frac{a^m}{a^n} = a^{m-n} .

Here, the base is 5, the exponent in the numerator is 3, and the exponent in the denominator is 8.

  • Apply the rule: 538 5^{3-8}
  • Subtract the exponents: 55 5^{-5} .

Therefore, the simplified expression is 55 5^{-5} .

The solution to the question is: 55 5^{-5}

Answer

55 5^{-5}